Tower of Confidence: Revealing the Impact of Transformational Leadership on Self-Efficacy - Nurlaelah; Unifah Rosyidi; Sukro Muhab; Ahmad Jauhari Hamid Ripki (South Sulawesi Education Development (SSED), 2024)
The purpose of this study was to find out how transformational leadership impacts the level of self-efficacy of teachers in Madrasah Ibtidaiyah (MI) in Karawang Regency. This research was conducted using the structural-partial least squares modeling equation (SEM-PLS). The study sample consisted of 130 randomly selected MI teachers. Four main dimensions are used to measure transformational leadership: ideal influence, inspirational motivation, intellectual stimulation, and individual attention. Teachers' self-efficacy is measured based on their confidence in the teacher's ability to overcome difficulty, strength of belief and generality. The results showed that transformational leadership has a positive and significant influence on teacher self-efficiency. The dimensions of ideal influence and inspirational motivation are the ones that contribute the most to improving the teacher's self-efficiency. It can be concluded that transformational leadership has a positive and significant effect on teachers' self-efficiency. Transformational leadership can provide ideal influence and inspirational motivation so that teachers' confidence in their ability to teach, manage the classroom, and interact with students increases.